Umbilical cord separation time, predictors and healing complications in newborns with dry care. - María Dolores López-Medina; Ana Belén López-Araque; Manuel Linares-Abad; Isabel María López-Medina (PLoS ONE)
Objective The objective of this study was to explore the umbilical cord separation time, predictors, and healing complications from birth until the newborn was one month old. Design A quantitative longitudinal observational analytical study by stratified random sample was adopted. Setting Public health system hospitals in southern Spain and at newborns' homes. Participants Between April 2016 and December 2017, the study included 106 neonates born after 35-42 weeks of gestation whose umbilical cord was cured with water and soap and dried later as well as newborns without umbilical canalisation whose mothers enjoyed a low-risk pregnancy. Methods The data collection procedure comprised two blocks: from birth to the time of separation of the umbilical cord and from cord separation to the first month of life of the newborn. Umbilical cord separation time was measured in minutes; socio-demographic and clinical characteristics were measured by means of questionnaires, and the external diameter of the umbilical cord was measured using an electronic stainless-steel calliper and trailing roller. Results The mean umbilical separation time: 6.61 days (±2.33, IC 95%:6.16-7.05). Incidence of omphalitis was 3.7%; granuloma was 8.6%. Separation time predictors were wetting recurrence, birth weight, intrapartum antibiotics, birth season, and Apgar < 9 (R2 = 0.439 F: 15.361, p <0.01). Conclusion The findings support the World Health Organization recommendations: dry umbilical cord cares is a safe practice that soon detaches the umbilical cord, taking into account the factors studied that will vary the length of time until the umbilical cord is separated.